Effect of Sheng-Jiang Powder on Gut Microbiota in High-Fat Diet-Induced NAFLD. (26th November 2020) - Li, Juan; Hu, Qian; Xiao-yu, Dai; Zhu, Lv; Miao, Yi-fan; Kang, Hong-xin; Zhao, Xian-lin; Yao, Jia-qi; Long, Dan; Tang, Wen-fu; Wan, Mei-hua
Abstract : Background and Aims . Nonalcoholic fatty liver disease (NAFLD) is an alarming global health problem that is predicted to be the major cause of cirrhosis, hepatocellular carcinoma, and liver transplantation by next decade. Gut microbiota have been revealed playing an important role in the pathogenesis of NAFLD. Sheng-Jiang Powder (SJP), an empirical Chinese medicine formula to treat NAFLD, showed great hepatoprotective properties, but the impact on gut microbiota has never been identified. Therefore, we performed this study to investigate the effect of SJP on gut microbiota in NAFLD mice. Methods . NAFLD was induced by 12 weeks' high-fat diet (HFD) feeding. Mice were treated with SJP/normal saline daily for 6 weeks. Blood samples were obtained for serum biochemical indices and inflammatory cytokines measurement. Liver tissues were obtained for pathological evaluation and oil red O staining. The expression of lipid metabolism-related genes was quantified by RT-PCR and Western blotting. Changes in gut microbiota composition were analyzed by the 16s rDNA sequencing technique. Results . HFD feeding induced significant increase in bodyweight and serum levels of TG, TC, ALT, and AST. The pathological examination revealed obvious hepatic steatosis in HFD feeding mice. Coadministration of SJP effectively protected against bodyweight increase and lipid accumulation in blood and liver. Increased expression of PPAR γ mRNA was observed in HFD feeding mice, but a steady elevation of PPAR γ protein level was only found in SJP-treated mice. Meanwhile, the expression of FASN was much higher in HFD feeding mice. Microbiome analysis revealed obvious changes in gut microbiota composition among diverse groups. SJP treatment modulated the relative abundance of short-chain fatty acids (SCFAs) producing bacteria, including norank-f- Erysipelotrichaceae and Roseburia . Conclusions . SJP is efficient in attenuating HFD-induced NAFLD, and it might be partly attributed to the regulation of gut microbiota.